Full duplex secret transmission scheme based on user cooperation - Xiao-lei KANG; Xin-sheng JI; Lu XIA; Kai-zhi HUANG (Tongxin xuebao)
Full-duplex artificial noise scheme can achieve a limited improvement while the interference power keeps increasing and the full-duplex gain is null.To solve these two problems,a full-duplex secure transmission scheme based on user cooperation was proposed,in which the full-duplex receiver used partial power to send artificial noise,and transmitted the downlink signal by the remaining power to the user who shared the same frequency.In order to maximize the system secrecy rate,the beam vector of the desired signal and the artificial noise were designed.Besides,the optimal power allocation factor was obtained by one-dimensional search simply.Simulation results show that compared with the RS-ref and HD methods,the proposed method can achieve an approximate linear growth in high power and can obtain the full-duplex gain.